Digital Transformation Towards Firm Value: The Moderating Role of Intellectual Capital Components - Helena Ali Tahara; Bima Cinintya Pratama; Azmi Fitriati; Ira Hapsari (Paradoks : Jurnal Ilmu Ekonomi, 2026)
Digital transformation is increasingly viewed as a source of corporate value creation; however, empirical evidence is mixed, suggesting that digitization does not automatically lead to increased corporate value. Based on the resource-based view, this study examines the role of intellectual capital, consisting of human capital, structural capital, and physical capital, in moderating the relationship between digital transformation and corporate value in the consumer non-cyclicals sector in Indonesia. This study uses 167 years of company observations from 2019 to 2023 and analyzes them using panel-data regression with firm fixed effects and cluster-robust standard errors in STATA. The results show that digital transformation and structural capital increase corporate value, while human capital has an adverse effect, and physical capital has no direct effect. Surprisingly, human capital actually weakens the effect of digital transformation on company value, whereas structural and physical capital strengthen this relationship. These findings theoretically extend the resource-based view by highlighting the heterogeneous and interactive role of intellectual capital in digital value creation. In practice, the results suggest that firms prioritize strengthening structural capital and ensuring the readiness of human resources to maximize the value-enhancing effects of digital transformation, particularly in emerging market contexts.